Letter to Editor: Requirement of National Organization of Ethics in Research - Abadi, Amin Talebi Bezmin (Archives of Advances in Biosciences, 2019)
Recently, Abbasiyan et al. published an interesting paper entitled “Do the Editors-in-Chief of Iranian Medical Journals have a Good Knowledge, Attitude and Practice of Plagiarism?”, addressing the ethical disputes occurred in last years in the Iranian research atmosphere [1]. In this study, authors nicely discussed the recent reports and flagged a critical suggestion for research decision-makers in Iran. Enjoo published a letter indicating on urgent need to have a new organization for having better situation [2]. Meantime, I think that newer policy help this idea before it can be widely referred. At first glance, there is an agreement that the current ethical administrative structure conducted by health ministry is basically well-structured. However, we expect this committee would possibly reduce the chance of the act of scientific misconducts. Though, I do not believe that current designed structure can be resulted in preventing the act of ethical misbehavior. From scientific point of view, it is long that everyone acknowledged that the scientific journals retract papers due to the various types of flaws include falsification, duplication, data manipulation and fabrication. The journal publishes a notice indicating a report of retraction, but it clearly sends a message that editors/reviewers (as a main scientific judge) are not efficiently involved in the review process [3, 4]. This is a neglected part of scientific publishing which always is far from the intense attention. Given new structure of ethical organization as termed ‘’ National Organization of Ethics in Research ‘’, training the editors and reviewers should be in the first priority. To now, researchers never got the credit or scores for their reviewing activities. Being ranked in the top list of the best accredited reviewers is a suggestion for science stakeholders to choose the best reviewers for national journals at least being a permanent member of editorial board. With this regard, Publons suggests the potential candidates to the senior editors in order to primary check the reviewers to be a member of editorial boards or blind reviewer process [5, 6]. The dark side of ethical issue is that we may not face with a real scientific researcher who commit such submissions or actually fraud! Indeed, it can raise another message that no specific education had been obliged for young researchers before they achieve the further promotions. Altogether, it can be concluded that asking independent advisors in design and develop this structure ‘’ National Organization of Ethics in Research ‘’ (NOER)is the most crucial step to have a new organization with scientific structure arranging and directing the such educations and ethical surveys for even senior professors in the national scale. Given the independency of NOER and independent advisors with proper background can help both ii) Ministry of Science, Research, and Technology to effectively prevent such bad news published in Nature and Science [7, 8].